1983
DOI: 10.1136/bmj.287.6388.318
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis: should we immunise neurologically disabled and developmentally delayed children?

Abstract: A total of 400 children with neurological disorders were studied to ascertain whether they had been immunised against pertussis, the reasons for non-immunisation, and the "validity" of these reasons, as judged by interpretation of the recommendations of the Department of Health and Social Security. The results for this group were compared with those for a group of 400 aged matched controls. The study group had a significantly lower rate of immunisation than controls (p < 001); rates for both groups fell sharpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…An English study from 1983, which reviewed the pertussis immunisation status of 400 children with a neurological condition, found that only 19% of children with CP were vaccinated . These historical data are difficult to compare to more recent studies as at that time the UK Department of Health recommended children with CP should not be vaccinated.…”
mentioning
confidence: 99%
“…An English study from 1983, which reviewed the pertussis immunisation status of 400 children with a neurological condition, found that only 19% of children with CP were vaccinated . These historical data are difficult to compare to more recent studies as at that time the UK Department of Health recommended children with CP should not be vaccinated.…”
mentioning
confidence: 99%
“…First, indicators of lower socio-economic position have been associated in the UK with lower childhood vaccination coverage rates (see above) and an increased prevalence of intellectual disability [16]. Second, there is some limited evidence that historically in the UK paediatricians may have advised parents of children with intellectual and developmental disabilities not to immunise [17].…”
Section: Introductionmentioning
confidence: 99%